A Review on Piccha Basti as a Pharacotherapeutic Option for Acute Inflammatory Conditions of Lower Gastrointestinal Tract - Nitin Jindal; Umesh Kumar Shukla (Journal of Ayurveda)
Objective:Piccha basti is a type of Niruha basti which has been described for ailments primarily related to the gastrointestinal tract. The present review has been made to explore Piccha basti as a pharmacotherapeutic option for acute inflammatory conditions of lower gastrointestinal (GI) tract. Data Source:Classical Ayurveda texts, including Brihattrayee along with their commentaries and Nighantus are the main data source for this review. The published articles related to Piccha basti, inflammatory bowel disease, and rectal therapy available in PubMed, Google Scholar, etc. have been also referred for this review. Different aspects related to Piccha basti like its nomenclature, ingredients, method of preparation and dose have been studied and analyzed which were available in classical texts. The supportive scientific studies related with main herbs of Piccha basti and the use of enema for inflammatory bowel disease in modern medicines are also explored for this review. Review Methods and Conclusion:Based on this review, it can be summarized that Piccha basti may be considered as a rectal drug delivery system having mucoadhesive properties which enable it to protect the colonic mucosa and perform various therapeutic actions in acute inflammatory conditions of the lower gastrointestinal tract. Dedicated clinical studies may be planned to establish its role in different acute inflammatory conditions of the lower GI tract.